2011
DOI: 10.1007/s10826-011-9509-5
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement and Depressive Symptoms in Low-Income Latino Youth

Abstract: The Latino population in the United States is increasing rapidly, and Latino youth comprise a significant proportion of the overall school-age population. Latino youth, however, demonstrate lower levels of academic achievement. Research also indicates Latino youth consistently report higher levels of depressive symptoms. We examined the relation between academic achievement and depressive symptoms in Latino youth. We additionally investigated the potential mediating role of academic selfefficacy and goal-orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 74 publications
(101 reference statements)
0
29
1
1
Order By: Relevance
“…However, little empirical research has been conducted to establish this relationship for this population. In a recent study, Zychinski and Polo (2012) found that for 133 fifth through seventh grade Latino students, higher reports of depressive symptoms significantly correlated with lower academic achievement. Similarly, Lobato et al (2011) found that Latino youth who had at least one sibling with an intellectual disability, reported higher levels of internalizing issues and lower levels of academic functioning.…”
Section: Mental Health Acculturative Stress and Academic Performancementioning
confidence: 96%
“…However, little empirical research has been conducted to establish this relationship for this population. In a recent study, Zychinski and Polo (2012) found that for 133 fifth through seventh grade Latino students, higher reports of depressive symptoms significantly correlated with lower academic achievement. Similarly, Lobato et al (2011) found that Latino youth who had at least one sibling with an intellectual disability, reported higher levels of internalizing issues and lower levels of academic functioning.…”
Section: Mental Health Acculturative Stress and Academic Performancementioning
confidence: 96%
“…Research on U.S. Hispanics has found a link between depressive symptoms and academic achievement (Zychinski and Polo 2012). A 5 years longitudinal study exploring the causal direction between depressive symptoms and academic outcomes in high school students concluded that depressive symptoms “preced[ed] and caus[ed] subsequent decreases in high school academic achievement in the form of GPA” and “not the other way around” (Hishinuma et al 2012, p. 1, 13).…”
Section: Introductionmentioning
confidence: 99%
“…The current study sought to understand the relationship between EI affirmation, psychological functioning (i.e., depression and life satisfaction), and academic outcomes (i.e., academic motivation, academic skepticism, academic expectations, and academic aspirations) for Latina/o youth. Previous literature has established a relationship between EI affirmation and psychological functioning (Rivas‐Drake et al, ), as well as a relationship between psychological functioning and academic outcomes (Balanga et al, ; Close & Solberg, ; Zychinski & Polo, ). Thus, a multiple mediation model was tested, which specifically hypothesized that the psychological functioning variables of depressive symptoms and life satisfaction would act as mediators between the relationship of EI affirmation and academic outcomes, and that academic attitudes would act as mediators between the relationship of psychological functioning (as measured by depressive symptoms and life satisfaction) and ambition for higher education.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, a significant relationship was found between depressive symptoms, life satisfaction, and academic attitudes, such that higher levels of life satisfaction were related to higher academic motivation and higher levels of depressive symptoms were related to higher levels of academic skepticism. These findings corroborate previous findings relating poorer psychological functioning to poorer academic outcomes and better psychological functioning to better academic outcomes (Balanga et al, ; Close & Solberg, ; Zychinski & Polo, ). If an individual reports higher levels of life satisfaction, they may feel more optimistic or positive about their future possibilities (McIlveen, Beccaria, & Burton, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation